Case report: Inflammatory sternoclavicular joint arthritis induced by an immune checkpoint inhibitor with remarkable responsiveness to infliximab - Kachi, Shion; Sumitomo, Shuji; Oka, Hideki; Hata, Akito; Ohmura, Koichiro (Frontiers in Immunology, 2024)
This report describes the case of a 48-year-old woman who presented with sternoclavicular joint arthritis after administration of an immune checkpoint inhibitor (ICI), durvalumab, for small cell lung carcinoma. The onset of arthritis transpired 18 months after the commencement of the ICI therapeutic regimen and demonstrated resilience to glucocorticoid treatment. After excluding infectious aetiologies and metastatic involvement, the patient was diagnosed with ICI-induced arthritis (ICI-IA). Considering the articular implications akin to the SAPHO syndrome, the patient was treated with infliximab, resulting in complete resolution. This finding implies that biological DMARDs can serve as effective interventions for ICI-induced sternoclavicular joint arthritis. Given the heterogeneous nature of its pathogenesis, the selection of therapeutic agents may require customization based on the distinct clinical presentation of each individual case.